A Multi-Site Survey Study of Patient Satisfaction with Teledermatology - Nwankwo, Christy; Houpe, Jessica E.; Ho, Bao Vincent K.; Seger, Edward W.; Wu, Dominic J; Rajpara, Anand (Kansas Journal of Medicine, 2022)
Introduction. Telemedicine has been of heightened focus due to spikes in usage during the COVID-19 pandemic. Disparities in health care may affect patient satisfaction with this resource depending on factors such as patient race, age, or socioeconomic background. The purpose of this study was to analyze patient satisfaction with teledermatology to identify any differences in satisfaction based on race, age, and income during the COVID-19 pandemic period. Methods. A 21-question, IRB-approved survey was administered to patients at two academic dermatology clinics in Kansas City. Patient satisfaction was measured using a five-point Likert scale. Results. A total of 64 completed surveys were analyzed (17.8% response rate). Most of the participants were female (n = 48, 75%), age 45 to 60 (n = 17, 26.6%), and reported White for race (n = 55, 85.9%). Overall, 73.4% (n = 47) of patients reported being satisfied with their visit. However, only 38.7% (n = 24) of participants were likely to choose a video over an in-person visit. Reasons for low patient satisfaction included concerns regarding ability to perform an accurate physical exam with a video visit (n = 9, 14.1%), receiving inadequate care (n = 4, 6.3%), protected privacy (n = 3, 4.7%), and provider understanding the patient (n = 2, 3.1%). Conclusions. Our findings were similar to prior studies stating no difference in patient satisfaction with regards to age, income, or race and patients reporting high satisfaction with teledermatology appointments despite a preference for in-person dermatology visits. Future studies with a larger diverse cohort of participants are needed to elucidate and address possible disparities associated with teledermatology use.